Sustainable Diet and Changes in Food Consumption in Chosen European Union Countries - Rejman, Krystyna; Halicka, Ewa; Kowrygo, Barbara (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2014)
The most important challenges of food policy and public health in the 21st Century include fighting high levels of obesity and food waste. Both issues are linked to the necessity of reducing greenhouse gas emissions and inhibiting climate change. Diet modification towards a more sustainable and healthy model, based in greater extent on plant-derived (vegetal) food and not animal products is seen as a chance to improve this situation. Taking these aspects into consideration, an analysis of consumption trends (1991-2011) of 6 food groups, known as markers of sustainable diet, was carried out in 7 EU countries. The study was based on FAO Food Balance Sheet statistical data. The current consumption structures in the selected countries was compared to recommended, sustainable and healthy diets. It was shown that in general homogenization of food consumption, a decrease of pulses and increase of fruit consumption had taken place. In each country the share of cereals & potatoes, fruit & vegetables, milk & dairy products, and meat did not meet the recommendations. The consumption of the first two groups was too low, the remaining two – too high.